Do Mothers or Children Lead the Dance? Disentangling Individual and Influence Effects During Conflict. Issue 2 (20th August 2020) - Sokolovic, Nina; Plamondon, Andre; Rodrigues, Michelle; Borairi, Sahar; Perlman, Michal; Jenkins, Jennifer M.
Abstract : Are mother–child conflict discussions shaped by time‐varying, reciprocal influences, even after accounting for stable contributions from each individual? Mothers were filmed discussing a conflict for 5 min, separately with their younger (ages 5–9, N  = 217) and older (ages 7–13, N  = 220) children. Each person's conflict constructiveness was coded in 20‐s intervals and data were analyzed using dynamic structural equation modeling, which separates individual and influence effects. Children influenced their mothers' behavior under certain conditions, with evidence for developmental differences in the magnitude and direction of influence, whereas mothers did not influence their children under any circumstance. Results are discussed in the context of child effects on parent behavior and changes in parenting across middle childhood.